The Strategy of Islamic Education Teachers in Internalizing the Values of Religious Moderation in the Learning of Islamic Education and Character Books - Dewi, Mifathul Jennah Rosifa; Zainab, Nurul; Sa'diyah, Halimatus (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2025)
Radical attitudes not only occur in society but also spread to education, this is because of the many cases of radicalism committed by teachers to their students or between students, so that moderation becomes important to be instilled in students from an early age, this study attempts to explore whether Education at SMPN 1 Sampang and SMPN 1 Tlanakan contains the values ​​of religious moderation in the PAI-BP textbooks that are taught as well as in order to find out the strategy for internalizing the values ​​of religious moderation carried out by PAI teachers. This study is a field research with a qualitative approach, that all forms of data in this study will be attached in the form of words. Primary data sources are taken from people who have specifically experienced the objects studied, including the principal, teachers and students, while the primary data sources in this study are supporting data in the form of literature, field notes or other supporting documents. Data collection in this study includes interviews, observations and documentation. After the data is collected, an analysis and checking of the validity of the data will be carried out by means of 1) consistency of observation and triangulation. The results of this study are: 1) The PAI-BP book at SMPN 1 Sampang and SMPN 1 Tlanakan schools contains material on religious moderation with details of three materials explaining directly and two materials being integrated. 2) The way teachers internalize the value of religious moderation is by providing equal rights and opportunities in learning, then using moderate language (from infidels to non-Muslims), and treating students in subtle ways. This study can contribute to institutions as a form of reference in internalizing the value of religious moderation to students through the methods offered in this study.